Efficacy and safety of two tip flexible suctioning ureteral access sheaths combined with a 7.5Fr flexible ureteroscope: a retrospective study - Luo, Jinquan; Li, Yueming; Lin, Jielin; Li, Xinyi; He, Wang; Yuan, Runqiang; Gong, Mancheng (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to compare the efficacy and safety of two tip-flexible suctioning ureteral access sheaths (TFS-UAS), 12/14Fr (Group A) and 10/12Fr (Group B), combined with a 7.5Fr flexible ureteroscope (f-URS) for treating upper ureteral and renal stones.MethodsA retrospective analysis of 168 patients undergoing retrograde intrarenal surgery (RIRS) was conducted. Group A (n = 76) used a 12/14Fr TFS-UAS, while Group B (n = 92) used a 10/12Fr TFS-UAS. Primary outcomes included stone-free rates (SFR) (Grade I: ≤2 mm; Grade II: ≤4 mm fragments), operative times, and complications.ResultsBaseline characteristics were comparable between groups. Group A demonstrated significantly shorter operation (72.5 vs. 78.5 min, P < 0.05) and lithotripsy durations (57.5 vs. 64.5 min, P < 0.05). Immediate SFR (Grade I) was higher in Group A (86.8% vs. 71.7%, P = 0.018), but 1-month SFR showed no difference (90.8% vs. 84.4%, P = 0.242). Grade II SFR and complication rates (ureteric injury, fever, sepsis) were similar (P > 0.05).ConclusionThe 12/14Fr TFS-UAS combined with a 7.5Fr f-URS offers superior lithotripsy efficiency and immediate SFR compared to the 10/12Fr variant, while maintaining comparable long-term outcomes and safety. These findings support its clinical preference for RIRS in upper tract calculi.